High-strength steel slag plate and forming method thereof
By adding amorphous SiO2 powder or beaded powder to the steel slag powder and vibrating the initial embryo of the steel slag during carbonation treatment, the problem of low strength of the traditional steel slag plate is solved, and the compressive strength and durability are significantly improved.
Patent Information
- Application Number
- CN202411718856.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The strength of the steel slag plate after traditional carbonation is not high, resulting in the product being fragile and poor durability.
By adding amorphous SiO2 powder or beaded powder to the steel slag powder as filler, and vibrating the steel slag initial embryo during carbonation treatment, forming a high-strength steel slag plate.
It significantly improves the compressive strength of the steel slag plate, reduces the generation of cracks during carbonation, improves the density of the material and carbon storage capacity, and enhances the durability and long-term effectiveness of the product.
Smart Images

Figure CN119551941A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of steel slag modification, and in particular to a high-strength steel slag plate and a forming method thereof. Background Art
[0002] Steel slag is a byproduct of the steel industry, and its emissions account for about 15% to 20% of the total steel production. my country's annual steel slag emissions are as high as more than 100 million tons, with a cumulative stockpile of more than 1 billion tons, and a comprehensive utilization rate of less than 30%. Most of the steel slag has not yet been comprehensively utilized. The large amount of stockpiled steel slag not only occupies land, wastes resources, and pollutes the environment, but also has serious safety hazards. Therefore, the steel industry is in urgent need of new technologies for environmentally friendly resource utilization of steel slag.
[0003] Carbonation treatment of steel slag is an effective method to improve the resource utilization of steel slag. The carbonation treatment mainly includes the steps of grinding the steel slag into powder - adding water and stirring - die-casting into billets - carbonization treatment. The carbonation treatment can reduce the content of free calcium oxide and magnesium oxide, and solve the problem of poor volume stability of steel slag. The steel slag plate formed after treatment can be converted into building materials or high value-added products, which can improve the utilization rate of steel slag.
[0004] However, the steel slag plate treated by carbonation in the traditional technology has the problem of low strength, which makes the formed product fragile and has poor durability during use.
[0005] In view of this, it is of great significance to provide a high-strength steel slag product. Summary of the invention
[0006] The purpose of the present application is to provide a steel slag plate and a forming method thereof, which can significantly improve the compressive strength of the steel slag plate.
[0007] In the first aspect, the present application provides a method for forming a high-strength steel slag plate using the following technical solution:
[0008] A method for forming a high-strength steel slag plate comprises the following steps:
[0009] Adding a silicon supplement to the steel slag powder and mixing them to obtain a powder mixture, wherein the silicon supplement comprises at least one of amorphous SiO2 powder and a precipitated bead powder;
[0010] adding water to the powder mixture and stirring to form a mortar mixture;
[0011] The mortar mixture is processed to form a slag board.
[0012] Furthermore, the steel slag powder is obtained by grinding converter steel slag, and the converter steel slag includes CaO, MgO, SiO2, and Fe2O3 in a mass ratio of 45-50:4-6:10-15:24-28, wherein CaO accounts for 45-50% of the mass of the steel slag powder.
[0013] Furthermore, the silicon supplement comprises amorphous SiO2 powder, and the mass content of the amorphous SiO2 powder is 0.2-1.5% of the steel slag powder.
[0014] Furthermore, the mass content of the amorphous SiO2 powder is 0.6-1.0% of the steel slag powder.
[0015] Furthermore, the silicon supplement also includes sedimentary bead powder, and the mass content of the sedimentary bead powder is 0.4-1.2% of the steel slag powder.
[0016] Furthermore, the mass content of the pellet powder is 0.6-1.0% of the steel slag powder.
[0017] Furthermore, the amorphous SiO2 powder and the precipitated ball powder are mixed in a mass ratio of 1:1 and added into the steel slag powder.
[0018] Further, the processing of the mortar mixture to form a slag board comprises:
[0019] Processing the mortar mixture to form a primary slag;
[0020] The steel slag embryo is subjected to carbonation treatment to form a steel slag plate, wherein the steel slag embryo is vibrated during the carbonation treatment.
[0021] Furthermore, the vibration frequency of the steel slag embryo is set to 150-350 Hz.
[0022] In a second aspect, the present application provides a high-strength steel slag plate, which is prepared using the above-mentioned high-strength steel slag plate forming method.
[0023] In summary, the present application includes at least one of the following beneficial technical effects:
[0024] 1. In the present application, amorphous SiO2 powder and / or sedimentary ball powder are used as fillers. Amorphous SiO2 and sedimentary ball powder can fill the pores of steel slag, reduce the internal porosity, and increase the density of the material, thereby improving the compressive strength of the pressed green body. In addition, the addition of amorphous SiO2 can also form a new mineral phase during the carbonation process, further improving the microstructure, and the addition of sedimentary ball powder can effectively improve the fluidity of the powder material and improve the strength and stability of the material.
[0025] 2. In this application, amorphous SiO2 powder and precipitated ball powder are used as fillers, which can provide additional reaction surface area during the carbonization process, increase the amount of CO2 solidified during the carbonation process, thereby improving the carbon sequestration capacity of steel slag and contributing more value to environmental protection and carbon reduction.
[0026] 3. In the present application, the steel slag blank will be vibrated when the steel slag blank is subjected to carbonation treatment. Mechanical vibration can promote CO2 to diffuse more evenly into the micropores of the steel slag blank, accelerate the carbonation reaction rate, and improve the overall carbonation efficiency. It also helps to rearrange the steel slag particles in the steel slag blank, promote the cleanliness of the carbonation product, and make the material structure more uniform.
[0027] 4. The mechanical vibration and silicon supplement in this application can not only improve the initial strength of the steel slag plate, but also reduce the generation of cracks during the carbonation process, thereby improving the durability and long-term effectiveness of the pressed green sheet, making it have better performance stability in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a bar graph of the compressive strength of the steel slag plate when the silicon supplement is set as amorphous SiO2 powder in the present application.
[0029] Figure 2 It is a line graph of CO2 absorption when the silicon supplement is set as amorphous SiO2 powder in the present application.
[0030] Figure 3 It is a bar graph of the compressive strength of the steel slag plate when the silicon supplement is set as the bead powder in the present application.
[0031] Figure 4 It is a line graph of CO2 absorption when the silicon supplement is set as a bead powder in this application.
[0032] Figure 5 It is a bar graph of the compressive strength of the steel slag plate when the silicon supplement is set as amorphous SiO2 powder and precipitated ball powder in the present application.
[0033] Figure 6 It is a line graph of CO2 absorption when the silicon supplement in this application is set as amorphous SiO2 powder and sedimentation bead powder.
[0034] Figure 7 It is a bar graph of the compressive strength of the steel slag plate after mechanical vibration in this application.
[0035] Figure 8 It is a line graph of the CO2 absorption amount after the steel slag plate is mechanically vibrated in this application.
[0036] Fig. 9 This is the microscopic morphology of Comparative Example 1.
[0037] Fig.10 This is the microscopic morphology of Example 20. DETAILED DESCRIPTION
[0038] The following will be combined with the attached Figure 1-10 The technical solution of the present application is described clearly and completely. The following embodiments are exemplary and are only used to explain the present application, and cannot be interpreted as limiting the present application. In the following description, the same symbols are used to represent the same or equivalent elements, and repeated descriptions are omitted.
[0039] In the description of the present application, it should be understood that the terms "upper", "lower", "inside", "outside", "left", "right", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, or are the orientations or positional relationships in which the products of the present application are conventionally placed when in use, or are the orientations or positional relationships conventionally understood by those skilled in the art. They are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0040] In addition, the terms "installed", "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0041] It should be further understood that the term “and / or” used in the specification and corresponding claims of this application refers to any and all possible combinations of one or more of the listed items.
[0042] Embodiment 1:
[0043] A method for forming a high-strength steel slag plate comprises the following steps:
[0044] S1. Take converter slag, wherein the converter slag includes CaO, MgO, SiO2, and Fe2O3, wherein CaO accounts for 47% of the mass of the slag powder, MgO accounts for 5% of the mass of the slag powder, SiO2 accounts for 13% of the mass of the slag powder, and Fe2O3 accounts for 26% of the mass of the slag powder;
[0045] S2, grinding the converter slag to obtain slag powder, wherein the grinding time is set to 18 minutes, at which time the particle size of the slag powder is measured, and the particle size of the slag powder is detected to be 55±10 μm;
[0046] S3, placing the steel slag powder in a 60°C electric constant temperature blast drying oven for drying at a temperature of 60±2°C for 24 hours to fully remove moisture from the steel slag powder;
[0047] S4, adding silicon supplement to the steel slag powder, wherein the silicon supplement is set to be amorphous SiO2 powder, the purity of the amorphous SiO2 powder is 98%, the particle size is 8000 mesh, and the mass content of the amorphous SiO2 powder added to the steel slag powder is 0.2% of the steel slag powder;
[0048] S5. The mixture of the slag powder and the SiO2 powder is subjected to ball mill stirring (mixing), the stirring speed is set to 150 r / min, and the stirring time is set to 20 min to obtain a powder mixture;
[0049] S6. Add water to the powder mixture and stir to form a mortar mixture, wherein the mass content of water added to the powder mixture is 10% of the powder mixture; during stirring, mechanical stirring is performed at a low speed of 150 r / min for 5 minutes;
[0050] S7, placing the mortar mixture in a mold and pressing it into shape, wherein the pressure during the pressing process is set to 0.7 MPa, and demolding is performed after holding the pressure for 120 seconds to obtain a steel slag embryo, and the compaction degree of the steel slag embryo is measured to be 60%;
[0051] S8, placing the steel slag embryo in a carbonation reaction chamber, and introducing CO2 gas into the carbonation reaction chamber, wherein the concentration of the CO2 gas is set to 99.99%, the pressure is set to 0.12 MPa, and the carbonation time is set to 7 hours to form a steel slag plate.
[0052] S9. Place the steel slag plate in a constant temperature drying oven for drying. The drying temperature is set to 60±2°C and the drying time is set to 7h.
[0053] Embodiment 2:
[0054] A method for forming a high-strength steel slag plate comprises the following steps:
[0055] S1. Take converter slag, wherein the converter slag includes CaO, MgO, SiO2, and Fe2O3, wherein CaO accounts for 50% of the mass of the slag powder, MgO accounts for 4% of the mass of the slag powder, SiO2 accounts for 15% of the mass of the slag powder, and Fe2O3 accounts for 28% of the mass of the slag powder.
[0056] S2, grinding the converter slag to obtain slag powder, wherein the grinding time is set to 15 minutes, at which time the particle size of the slag powder is measured, and the particle size of the slag powder is detected to be 65±10 μm;
[0057] S3, placing the steel slag powder in a 60°C electric constant temperature blast drying oven for drying at a temperature of 60±2°C for 24 hours to fully remove moisture from the steel slag powder;
[0058] S4, adding silicon supplement to the steel slag powder, wherein the silicon supplement is set to be amorphous SiO2 powder, the purity of the amorphous SiO2 powder is 98%, the particle size is 8000 mesh, and the mass content of the amorphous SiO2 powder added to the steel slag powder is 0.2% of the steel slag powder;
[0059] S5. The mixture of the slag powder and the SiO2 powder is subjected to ball mill stirring (mixing), the stirring speed is set to 200 r / min, and the stirring time is set to 15 min to obtain a powder mixture;
[0060] S6. Add water to the powder mixture and stir to form a mortar mixture, wherein the mass content of water added to the powder mixture is 12% of the powder mixture; during stirring, mechanical stirring is performed at a low speed of 200 r / min for 3 minutes;
[0061] S7, placing the mortar mixture in a mold and pressing it into shape, wherein the pressure during the pressing process is set to 0.9 MPa, and demolding after holding the pressure for 90 seconds to obtain a steel slag embryo;
[0062] S8, placing the steel slag embryo in a carbonation reaction chamber, and introducing CO2 gas into the carbonation reaction chamber, wherein the concentration of the CO2 gas is set to 99.99%, the pressure is set to 0.15 MPa, and the carbonation time is set to 9 hours, to form a steel slag plate.
[0063] S9. Place the steel slag plate in a constant temperature drying oven for drying. The drying temperature is set to 60±2°C and the drying time is set to 6h.
[0064] Embodiment 3:
[0065] A method for forming a high-strength steel slag plate comprises the following steps:
[0066] S1. Take converter slag, wherein the converter slag includes CaO, MgO, SiO2, and Fe2O3, wherein CaO accounts for 48% of the mass of the slag powder, MgO accounts for 6% of the mass of the slag powder, SiO2 accounts for 10% of the mass of the slag powder, and Fe2O3 accounts for 24% of the mass of the slag powder.
[0067] S2, grinding the converter slag to obtain slag powder, wherein the grinding time is set to 20 minutes, at which time the particle size of the slag powder is measured, and the particle size of the slag powder is detected to be 50±10 μm;
[0068] S3, placing the steel slag powder in a 60°C electric constant temperature blast drying oven for drying at a temperature of 60±2°C for 24 hours to fully remove moisture from the steel slag powder;
[0069] S4, adding silicon supplement to the steel slag powder, wherein the silicon supplement is set to be amorphous SiO2 powder, the purity of the amorphous SiO2 powder is 98%, the particle size is 8000 mesh, and the mass content of the amorphous SiO2 powder added to the steel slag powder is 0.2% of the steel slag powder;
[0070] S5. The mixture of the slag powder and the SiO2 powder is subjected to ball mill stirring (mixing), the stirring speed is set to 180 r / min, and the stirring time is set to 30 min to obtain a powder mixture;
[0071] S6. Add water to the powder mixture and stir to form a mortar mixture, wherein the mass content of water added to the powder mixture is 8% of the powder mixture; during stirring, mechanical stirring is performed at a low speed of 180 r / min for 4 minutes;
[0072] S7, placing the mortar mixture in a mold and pressing it into shape, wherein the pressure during the pressing process is set to 0.6 MPa, and demolding after holding the pressure for 100 seconds to obtain a steel slag embryo;
[0073] S8, placing the steel slag embryo in a carbonation reaction chamber, and introducing CO2 gas into the carbonation reaction chamber, wherein the concentration of the CO2 gas is set to 99.99%, the pressure is set to 0.10 MPa, and the carbonation time is set to 3 hours, to form a steel slag plate.
[0074] S9. Place the steel slag plate in a constant temperature drying oven for drying. The drying temperature is set to 60±2°C and the drying time is set to 8h.
[0075] Embodiment 4:
[0076] A method for forming a high-strength steel slag plate is the same as that of Example 1, except that the mass content of amorphous SiO2 powder is 0.4% of the steel slag powder.
[0077] Embodiment 5:
[0078] A method for forming a high-strength steel slag plate is the same as that of Example 1, except that the mass content of amorphous SiO2 powder is 0.6% of the steel slag powder.
[0079] Embodiment 6:
[0080] A method for forming a high-strength steel slag plate is the same as that of Example 1, except that the mass content of amorphous SiO2 powder is 0.8% of the steel slag powder.
[0081] Embodiment 7:
[0082] A method for forming a high-strength steel slag plate is the same as that of Example 1, except that the mass content of amorphous SiO2 powder is 1.0% of the steel slag powder.
[0083] Embodiment 8:
[0084] A method for forming a high-strength steel slag plate is the same as that of Example 1, except that the mass content of amorphous SiO2 powder is 1.2% of the steel slag powder.
[0085] Embodiment 9:
[0086] A method for forming a high-strength steel slag plate is the same as that of Example 1, except that the mass content of amorphous SiO2 powder is 1.5% of the steel slag powder.
[0087] Embodiment 10:
[0088] A method for forming a high-strength steel slag plate is the same as Example 1, except that the silicon supplement is set as a sedimentation bead powder, and the mass content of the sedimentation bead powder is 0.4% of the steel slag powder.
[0089] Among them, sinking beads are a type of fly ash.
[0090] Specifically, fly ash is classified according to density, and fly ash is divided into sinking beads and floating beads. Floating beads are hollow glass microspheres with a density of less than 1 g / cm3 and can float on the water surface. Sinking beads have a density greater than 1 g / cm3 and will sink in water. Its structure is relatively dense and does not have the hollow characteristics of floating beads.
[0091] Embodiment 11:
[0092] A method for forming a high-strength steel slag plate is the same as Example 10, except that the mass content of the precipitated ball powder is 0.6% of the steel slag powder.
[0093] Embodiment 12:
[0094] A method for forming a high-strength steel slag plate is the same as Example 10, except that the mass content of the bead powder is 0.8% of the steel slag powder.
[0095] Embodiment 13:
[0096] A method for forming a high-strength steel slag plate is the same as Example 10, except that the mass content of the precipitated ball powder is 1.0% of the steel slag powder.
[0097] Embodiment 14:
[0098] A method for forming a high-strength steel slag plate, which is the same as Example 10, except that the mass content of the bead powder is 1.2% of the steel slag powder
[0099] Embodiment 15:
[0100] A forming method for a high-strength steel slag plate is the same as Example 1, except that the silicon supplement is set as amorphous SiO2 powder and sedimentary ball powder, the amorphous SiO2 powder and the sedimentary ball powder are mixed in a mass ratio of 1:1 and added to the steel slag powder, and the mass content of the amorphous SiO2 powder and the sedimentary ball is set to 0.4% of the steel slag powder.
[0101] Embodiment 16:
[0102] A method for forming a high-strength steel slag plate is the same as Example 15, except that the mass content of amorphous SiO2 powder and sedimentary beads is set to 0.6% of the steel slag powder.
[0103] Embodiment 17:
[0104] A method for forming a high-strength steel slag plate is the same as Example 15, except that the mass content of amorphous SiO2 powder and precipitated beads is set to 0.8% of the steel slag powder.
[0105] Embodiment 18:
[0106] A method for forming a high-strength steel slag plate is the same as Example 15, except that the mass content of amorphous SiO2 powder and precipitated beads are both set to 1.0% of the steel slag powder.
[0107] Embodiment 19:
[0108] A method for forming a high-strength steel slag plate is the same as that of Example 16, except that the steel slag embryo is vibrated during the process of carbonation treatment of the steel slag embryo to form the steel slag plate. The vibration frequency of the steel slag embryo is set to 300 Hz.
[0109] Embodiment 20:
[0110] A method for forming a high-strength steel slag plate is the same as that of Example 17, except that the steel slag embryo is vibrated during the process of carbonation treatment of the steel slag embryo to form the steel slag plate. The vibration frequency of the steel slag embryo is set to 300 Hz.
[0111] Embodiment 21:
[0112] A method for forming a high-strength steel slag plate is the same as that of Example 18, except that the steel slag embryo is vibrated during the process of carbonation treatment of the steel slag embryo to form the steel slag plate. The vibration frequency of the steel slag embryo is set to 300 Hz.
[0113] Embodiment 22:
[0114] A method for forming a high-strength steel slag plate is the same as Example 20, except that the vibration frequency of the steel slag embryo is set to 150 Hz.
[0115] Embodiment 23:
[0116] A forming method of a high-strength steel slag plate is the same as that of Example 20, except that the vibration frequency of the steel slag embryo is set to 350 Hz.
[0117] Comparative Example 1: A method for forming a high-strength steel slag plate, which is the same as Example 1, except that no silicon supplement is added.
[0118] Compressive strength test: The compressive strength of the slag plate was measured using a universal press.
[0119] 1) Steel slag plates were prepared according to Comparative Example 1 and Examples 1-7, and the obtained steel slag plates were subjected to weight gain rate and compressive strength tests. The test data are shown in Table 1. A bar graph and a line graph were drawn based on the obtained test data. Figure 1-2 shown.
[0120] Table 1
[0121]
[0122]
[0123] According to Table 1, compared with Comparative Example 1, after adding amorphous SiO2 powder, the average weight gain rate of Example 1 and Examples 4-7 when forming the steel slag plate is improved, that is, the ability to solidify CO2 gas is improved. The reason is that the increase of amorphous SiO2 powder can provide additional reaction surface area during the carbonization process, thereby increasing the solidification amount of CO2 during the carbonation process, thereby improving the carbon sequestration capacity of the steel slag; among them, when the addition amount of amorphous SiO2 powder is 0.8% of the steel slag powder, compared with Comparative Example 1, the average weight gain rate is increased by 7.42%;
[0124] Compared with comparative example 1, after adding amorphous SiO2 powder, the compressive strength of the steel slag board after forming was significantly improved in Examples 1 and Examples 4-9. With the increase of amorphous SiO2 powder, the weight gain rate and compressive strength of the steel slag board increased first and then decreased.
[0125] Among them, when the amorphous SiO2 powder is set in the range of 0.6-1.0% of the steel slag powder (ie, Examples 5-7), the weight gain rate and compressive strength of the steel slag board are significantly improved.
[0126] First, although the difference in the addition amount between Example 5 and Example 4 is only 0.2%, the degree of enhancement in the compressive strength of Example 5 is 3 times that of Example 4, showing a significant improvement; secondly, the compressive strength performance of the steel slag plate prepared in Example 6 is the best, which is improved by 51.61% compared with Comparative Example 1.
[0127] 2) Steel slag plates were prepared according to the methods of Examples 10-14, and the weight gain rate and compressive strength tests of the obtained steel slag plates were performed, and compared with the data of Comparative Example 1. The test data are shown in Table 2. A bar graph and a line graph were drawn based on the obtained test data. Figure 3-4 shown.
[0128] Table 2
[0129]
[0130] According to Table 2, compared with Comparative Example 1, after adding the bead powder, the average weight gain rate of Examples 10-14 during the forming of the steel slag plate was improved. The reason is that the increase of the bead powder can also provide additional reaction area during the carbonization process, thereby improving the carbon sequestration capacity of the steel slag. Compared with Comparative Example 1, the average weight gain rate increased by 4.48%;
[0131] At the same time, the addition of the bead powder can effectively improve the fluidity of the powder material and enhance the strength and stability of the material. Compared with Comparative Example 1, after the bead powder was added, when the steel slag board was formed, the compressive strength of the steel slag board after forming was improved, and with the increase of amorphous SiO2 powder, the weight gain rate and compressive strength of the steel slag board showed a trend of first increasing and then decreasing.
[0132] Among them, when the bead powder is set to the range of 0.6-1.0% of the steel slag powder (i.e., Examples 11-13), the weight gain rate and compressive strength of the steel slag board are more prominent. First, compared with Example 10, although the difference in the amount of addition between Example 11 and Example 10 is only 0.2%, the degree of compressive strength enhancement of Example 11 is nearly 7 times that of Example 10, which is greater than the difference between Example 5 and Example 4, showing a significant improvement; secondly, the compressive strength performance of the steel slag board prepared in Example 12 is the best, which is 28.43% higher than that of Comparative Example 1.
[0133] It is also necessary to find that the weight gain rate and compressive strength of Examples 10-14 are smaller than those of Examples 1 and 4-9. This is because the amorphous SiO2 powder has a smaller particle size than the bead powder. In terms of mass ratio, the amorphous SiO2 powder can provide more additional reaction area.
[0134] However, although the steel slag board formed by adding sinking ball powder has a disadvantage in compressive strength compared to that formed by adding amorphous SiO2 powder, the steel slag board formed by adding sinking ball powder has better fluidity, so that the steel slag board formed by adding sinking ball powder can be used as a profile for 3D printing, and has a good application scenario in the field of 3D printing.
[0135] 3) Steel slag plates were prepared according to the methods of Examples 15-18, and the weight gain rate and compressive strength tests of the obtained steel slag plates were performed, and compared with the data of Comparative Example 1. The test data are shown in Table 3. A bar graph and a line graph were drawn based on the obtained test data. Figure 5-6 shown.
[0136] Table 3
[0137]
[0138] According to Table 3, compared with Comparative Example 1, after adding amorphous SiO2 powder and bead powder at the same time, the weight gain rate and compressive strength of the slag board in Examples 15-18 are improved. The weight gain rate and compressive strength of the slag board change with the increase of the amount of amorphous SiO2 powder and bead powder, which is the same as that of Examples 4-9 and Examples 10-14.
[0139] Among them, when the amount of amorphous SiO2 powder and bead powder added is small, the compressive strength of the formed steel slag board can be significantly enhanced, and Example 15 is the most prominent. Specifically, the compressive strength enhancement degree of Example 15 is 3.18% higher than the sum of the compressive strength enhancement degree of Example 4 and Example 10. That is, when the amount of silicon supplement added is small, adding amorphous SiO2 powder and bead powder at the same time can significantly improve the compressive strength of the steel slag board compared with adding amorphous SiO2 powder or bead powder alone.
[0140] In addition, compared with Example 1, Example 4-9, and Example 10-14, that is, when the amount of silicon supplement added is the same, the weight gain rate and the degree of compressive strength enhancement of Examples 15-18 are further improved when amorphous SiO2 powder and sinking ball powder are added at the same time compared to adding amorphous SiO2 powder or sinking ball powder alone.
[0141] This is because the addition of amorphous SiO2 powder and precipitated powder provides more reaction area and improves the fluidity of the steel slag embryo. Among them, the weight gain rate and compressive strength enhancement degree of Example 17 are the highest, with the weight gain rate increased to 7.84% and the compressive strength enhancement degree increased to 55.83%.
[0142] 4) Steel slag plates were prepared according to the methods of Examples 19-21, and the obtained steel slag plates were subjected to compressive strength tests. The test data are shown in Table 4. A bar graph and a line graph were drawn based on the obtained test data. Figure 7-8 shown.
[0143] Table 4
[0144]
[0145]
[0146] It can be seen from Table 4 that Example 19 is compared with Example 16, Example 20 is compared with Example 17, and Example 21 is compared with Example 18, that is, under the condition of the same silicon supplement content, vibrating the steel slag embryo during the carbonization process further improves the weight gain rate of the formed steel slag board and the compressive strength of the steel slag board.
[0147] Compared with the case without vibration, the average weight gain rate increased by 0.04%, and the average compressive strength increased by 1.68MPa. Among them, the compressive strength improvement effect of Example 21 is the best, with the compressive strength increased by 8.6% compared with Example 15 and 69.34% compared with Comparative Example 1, further improving the performance upper limit of the slag board. Fig. 9 and Fig.10 It can be seen from the microscopic morphology that compared with the steel slag plate formed in comparative example 1, the stacking between particles in Example 20 is denser and tighter.
[0148] This is because vibrating the steel slag embryo during the carbonization process can promote CO2 to diffuse more evenly into the micropores of the steel slag, accelerate the carbonation reaction rate, and improve the overall carbonation efficiency. At the same time, it also helps to rearrange the steel slag particles, promote the cleanliness of the carbonation product, make the material structure more uniform, and reduce the generation of cracks during the carbonation process, thereby improving the durability and long-term effectiveness of the steel slag board. That is, the steel slag board formed after adding the vibration step has better performance stability in practical applications.
[0149] The embodiments of this specific implementation are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. The same components are represented by the same figure marks. Therefore, any equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A method for forming a high-strength steel slag plate, characterized in that: The following steps are involved: Adding a silicon supplement to the steel slag powder and mixing them to obtain a powder mixture, wherein the silicon supplement comprises at least one of amorphous SiO2 powder and a precipitated bead powder; adding water to the powder mixture and stirring to form a mortar mixture; The mortar mixture is processed to form a slag board.
2. The method for forming a high-strength steel slag plate according to claim 1, characterized in that: The steel slag powder is obtained by grinding converter steel slag, and the converter steel slag includes CaO, MgO, SiO2, and Fe2O3 in a mass ratio of 45-50:4-6:10-15:24-28, wherein CaO accounts for 45-50% of the mass of the steel slag powder.
3. The method for forming a high-strength steel slag plate according to claim 1, characterized in that: The silicon supplement comprises amorphous SiO2 powder, and the mass content of the amorphous SiO2 powder is 0.2-1.5% of the steel slag powder.
4. The method for forming a high-strength steel slag plate according to claim 3, characterized in that: The mass content of the amorphous SiO2 powder is 0.6-1.0% of the steel slag powder.
5. A method for forming a high-strength steel slag plate according to any one of claims 3 or 4, characterized in that: The silicon supplement also includes a precipitated bead powder, and the mass content of the precipitated bead powder is 0.4-1.2% of the steel slag powder.
6. The method for forming a high-strength steel slag plate according to claim 5, characterized in that: The mass content of the precipitated beads powder is 0.6-1.0% of the steel slag powder.
7. The method for forming a high-strength steel slag plate according to claim 5, characterized in that: The amorphous SiO2 powder and the precipitated ball powder are mixed in a mass ratio of 1:1 and added into the steel slag powder.
8. The method for forming a high-strength steel slag plate according to claim 1, characterized in that: The method of processing the mortar mixture to form a slag board comprises: Processing the mortar mixture to form a steel slag embryo; The steel slag embryo is subjected to carbonation treatment to form a steel slag plate, wherein the steel slag embryo is vibrated during the carbonation treatment.
9. The method for forming a high-strength steel slag plate according to claim 8, characterized in that: The vibration frequency of the steel slag embryo is set to 150-350 Hz.
10. A high-strength steel slag plate, characterized in that: The high-strength steel slag plate is prepared by the molding method of any one of claims 1 to 9.
Citation Information
Patent Citations
Building material prepared by synergistic carbonization of steel slag, desulfurized gypsum and fly ash and method
CN112430051A
Method for improving carbonization rate and performance of steel slag sample
CN114195430A
Preparation method of high-strength carbonated steel slag plate
CN115504761A
Quantitative regulation and control method for compressive strength and CO2 absorptivity of carbonated steel slag product
CN117585928A
Carbonation treatment method of steel slag
JP2016037409A
Cited By
Special casting powder for non-oriented high-grade silicon steel for new energy automobile motor
CN120715182A